Civil Lawsuits Against Business Entities in Judicial Practice - Natasya Yunita Sugiastuti; Rafiqi; Andria Marchelia; Markus Suryoutomo; Rizki Wahyudi (Universitas Muhammadiyah Palu, 2026)
Unlawful acts constitute one of the fundamental bases for civil litigation within the Indonesian civil law system, particularly when the defendant is a business entity. In judicial practice, business entities as legal persons are frequently involved in commercial activities that may result in losses to other parties, including consumers, business partners, and the broader public. Consequently, claims based on unlawful acts serve as an essential legal mechanism to seek accountability for conduct that violates legal norms and causes damage. This article aims to examine the procedural framework for filing unlawful act claims against business entities in civil courts, to analyze the legal elements that must be established, and to identify evidentiary challenges commonly encountered during litigation. The research adopts a normative juridical method, employing statutory analysis, legal doctrines, and a review of relevant court decisions. The findings indicate that unlawful act claims against business entities tend to be more complex than those directed at individual defendants, particularly in proving the element of fault and establishing a causal link between the conduct and the resulting harm. Moreover, divergent judicial interpretations of the elements of unlawful acts contribute to inconsistencies in court rulings. Judicial decisions in cases involving unlawful acts committed by business entities have significant implications for legal certainty, the protection of injured parties’ rights, and the development of standards of legal responsibility in the business sector. Therefore, a comprehensive understanding of the construction of unlawful act claims, along with a strengthened judicial role, is essential to ensure justice and legal certainty in civil law enforcement.